2023
DOI: 10.1080/07853890.2022.2164610
|View full text |Cite
|
Sign up to set email alerts
|

Addition of venetoclax to myeloablative conditioning regimens for allogeneic hematopoietic stem cell transplantation in high-risk AML

Abstract: Background Venetoclax monotherapy is an effective option for patients with acute myeloid leukemia (AML). Venetoclax has also been used in non-myeloablative conditioning allogeneic hematopoietic stem cell transplantation (allo-HSCT) for high-risk AML with a tolerable toxicity profile. However, the efficacy and safety of a venetoclax-containing myeloablative conditioning (MAC) allo-HSCT regimen for high-risk AML have not been evaluated. Objective To evaluate the safety an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In addition, Handgretinger [22] estimates that more than half of all HLA haplotype-mismatched transplants will be performed worldwide following similar protocols. Previous studies at our center demonstrated that conditioning regimens based on GIAC achieved favorable engraftment, OS, and an acceptable morbidity of GVHD among allo-HSCT patients [23][24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Handgretinger [22] estimates that more than half of all HLA haplotype-mismatched transplants will be performed worldwide following similar protocols. Previous studies at our center demonstrated that conditioning regimens based on GIAC achieved favorable engraftment, OS, and an acceptable morbidity of GVHD among allo-HSCT patients [23][24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Venetoclax with azacitidine is a new first-line therapeutic option for patients with AML ineligible for intensive chemotherapy based on the VIALE-A trial and it has also been studied in combination with low-dose ara-C and IDH inhibitors in the up-front setting ( 56 , 168 , 169 ). In the transplant setting, venetoclax has been studied in combination with RIC and MAC chemotherapy regimens in patients with high-risk myeloid malignancies ( 65 , 170 ). The VIALE-T study is recruiting patients to study venetoclax with azacitidine maintenance versus standard best supportive care after alloHSCT (NCT04161885).…”
Section: Targeted Therapy In the Post-transplant Settingmentioning
confidence: 99%
“…The 1-year OS was 84%, with relapse incidence (RI) of 13% and NRM of 10%. Another study in younger patients (median age 25) reported outcomes of venetoclax with MAC in 31 high-risk AML patients who underwent their first alloHCT with low 600-day RI and NRM, 6.9% and 11.7%, respectively [ 44 ]. Of note, most patients received haploidentical transplant and high-risk AML was defined as refractory or relapsed AML, MRD-positive at transplantation, or adverse ELN risk.…”
Section: Novel Conditioning Approachesmentioning
confidence: 99%